2017
DOI: 10.1038/gim.2016.210
|View full text |Cite
|
Sign up to set email alerts
|

The current state of implementation science in genomic medicine: opportunities for improvement

Abstract: Although genomic discovery provides the potential for population health benefit, the current knowledge base around implementation to turn this promise into a reality is severely limited. Current gaps in the literature demonstrate a need to apply implementation science principles to genomic medicine in order to deliver on the promise of precision medicine.Genet Med advance online publication 12 January 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 18 publications
3
114
0
Order By: Relevance
“…For example, Roberts et al concluded from a literature review that “although genomic discovery provides the potential for population health benefit, the current knowledge base around implementation to turn this promise into a reality is severely limited” (23). Another example is our findings on comparative effectiveness research studies of precision medicine, based on a structured literature review and expert assessment of gaps (24).…”
Section: Precision Medicine – Where Are We Today?mentioning
confidence: 99%
“…For example, Roberts et al concluded from a literature review that “although genomic discovery provides the potential for population health benefit, the current knowledge base around implementation to turn this promise into a reality is severely limited” (23). Another example is our findings on comparative effectiveness research studies of precision medicine, based on a structured literature review and expert assessment of gaps (24).…”
Section: Precision Medicine – Where Are We Today?mentioning
confidence: 99%
“…It is currently unclear who is the best genomic interlocutor of the patient/individual (trained clinicians, genetic counselors and others) and how best to implement the use of genomic information. A systematic review of 283 implementation studies for genetic information concludes that there is very weak evidence and no solid conclusions (8). The complexity of interpreting genomic information (9) makes simplified solutions unrealistic.…”
Section: Should the Principles Of Evidence-based Medicine Change Withmentioning
confidence: 99%
“…Roberts et al 5 published a systematic review exam- iningthe current state ofthe field of implementation science in genomic medicine. In 2014, 283 published articles evaluated implementation of genomic medicine.…”
Section: What Is the Status Of The Evidence Base In Genomic Medicine?mentioning
confidence: 99%
“…Only a few studies attempted to develop and evaluate evidence-based strategies that can improve implementation of genomic medicine. The authors concluded that “the current knowledge base around implementation science to turn the promise of genomic medicine into reality is severely limited” 5 …”
Section: What Is the Status Of The Evidence Base In Genomic Medicine?mentioning
confidence: 99%